Clinical trials: their contribution to the efficiency of the clinical management of rheumatoid arthritis - Cristina P Alcañiz Escandell; José A Román Ivorra (BioExcel Publishing Ltd, 2019)
Background: This article presents a descriptive analysis of our Clinical Research Unit (CRU) at the Rheumatology Department in the University and Polytechnic Hospital La Fe (RD-UPH La Fe), Valencia (Spain), as well as an estimation of the economic impact of conducting clinical trials for the Spanish Health System in terms of avoided costs. Methods: During the period 2011-2015, a retrospective observational study was conducted based on the trials performed in our CRU, along with a cost analysis from the health authority perspective. Results: Most of the trials conducted during this period were phase III studies in patients with rheumatic disorders, particularly rheumatoid arthritis. An economic evaluation study showed that the implementation of these studies in our CRU resulted in an annual saving of €13,935.30 per patient. Conclusion: Our CRU is an efficacy and efficiency tool for cost saving in the healthcare system.